Protein and isozyme patterns of Fusarium oxysporum f. sp. ciceri isolates causing chickpea wilt - and S.S. MANE, N.B. PAWAR* (Indian Phytopathology, 2014)
Variations among different isolates of Fusarium oxysporum f. sp. ciceri collected from various locations of Maharashtra were studied in respect of protein and isozyme analysis. Protein content in different isolates ranged from 0.454 to 1.092 mg/100 mg mycelium and maximum protein content was observed in F23 isolates of F. oxysporum f. sp. ciceri and peroxidase activities ranged between 28.70 to 74.52 U min-1 mg-1 protein. The maximum polyphenol oxidase activity (1.86 U min-1 mg-1 protein) was observed in weakly pathogenic F5 isolate of Akola district. Maximum esterase activity was observed in weakly pathogenic isolate F54 of Satara district (16.23 Âµm min-1 mg-1 protein). Electrophoretic studies using SDS-PAGE revealed that, ten soluble proteins bands between molecular weights 44.67 to 112.2 KDa were detected in the isolates of F. oxysporum f. sp. ciceri, with high molecular weight protein bands specially expressed in highly virulent culture of Akola district (F1). Presence or absence of specific protein and isozyme bands measures variability and relatedness. No consistent appearance of esterase and polyphenol oxidase isozyme bands was visualized in the different pathogenic groups, which indicates variability among the isolates with respect to only one band was observed of the isolates.